1972
DOI: 10.1113/jphysiol.1972.sp010041
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of post‐ganglionic motor transmission in vas deferens by indirectly acting sympathomimetic drugs

Abstract: SUMMARY1. Using field stimulation with short trains of pulses (< 10 per train), the post-ganglionic motor transmission in the mammalian vas deferens has been further analysed pharmacologically.2. In preparations taken from guinea-pigs, rats and rabbits the effects of the indirectly sympathomimetic drugs, tyramine and cocaine, could be explained entirely on the basis of the actions of released, endogenous noradrenaline.3. Tyramine produced a contraction in vasa taken from normal rats but not from normal guinea-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
46
1

Year Published

1975
1975
1992
1992

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(55 citation statements)
references
References 6 publications
8
46
1
Order By: Relevance
“…In agreement with the observations of Ambache et al (1972) a-adrenoceptors is very likely since it was antagonized by yohimbine, which antagonizes these receptors at much lower concentrations than are required to antagonize actions at postsynaptic a-adrenoceptors a to be less in those (Starke, Borowski & Endo, 1975;Marshall, Nasmyth, a-methyl-p-tyrosine Nicholl & Shepperson, 1978). Also typical of the inhiwith reserpine alone bition of the output of transmitter produced by stimus it significant in these lation of presynaptic a-adrenoceptors was the fact that the inhibition was frequency-dependent, being J their increased rate greatest at low and least at high frequencies of stimu-,ontinuous stimulation lation.…”
Section: Dicussionsupporting
confidence: 68%
See 1 more Smart Citation
“…In agreement with the observations of Ambache et al (1972) a-adrenoceptors is very likely since it was antagonized by yohimbine, which antagonizes these receptors at much lower concentrations than are required to antagonize actions at postsynaptic a-adrenoceptors a to be less in those (Starke, Borowski & Endo, 1975;Marshall, Nasmyth, a-methyl-p-tyrosine Nicholl & Shepperson, 1978). Also typical of the inhiwith reserpine alone bition of the output of transmitter produced by stimus it significant in these lation of presynaptic a-adrenoceptors was the fact that the inhibition was frequency-dependent, being J their increased rate greatest at low and least at high frequencies of stimu-,ontinuous stimulation lation.…”
Section: Dicussionsupporting
confidence: 68%
“…It seemed possible that the twitch responses were only reduced because the synthesis of noradrenaline could still take place and that this synthesis was sufficient to maintain a reduced response. With this possibility in mind, the experiments of Ambache et al, (1972) have been repeated in the mouse vas and, additionally, noradrenaline synthesis has been blocked with a-methyl-p-tyrosine. A preliminary account of some of these results has appeared elsewhere (Marshall, Nasmyth & Shepperson, 1977 To block the activity of tyrosine hydroxylase, which is the rate limiting enzyme in the synthesis of noradrenaline (Levitt, Spector, Sjoerdsma & Udenfriend, 1965), L-o-methyl-p-tyrosine (200 mg/kg) was given intraperitoneally 4, 2 and 1 h before the animals were killed.…”
Section: Introductionmentioning
confidence: 99%
“…The fact that clonidine did not cause a contraction of the vas deferens and that the presynaptic inhibition was antagonized by phentolamine despite the presence of a postsynaptic aadrenoceptor (Gillespie & McGrath, 1975) reflected the unusual nature of the motor response in the vas deferens. The role of noradrenaline in the transmission process of the vas deferens has been questioned by Ambache & Zar (1971) and Ambache, Dunk, Verney & Zar, (1972). If however, as suggested by Gillespie & McGrath (1975), noradrenaline is the transmitter a possible explanation could be that hypogastric nerves have a very high population of presynaptic aadrenoceptors in comparison with other sympathetic nerves or that the postsynaptic a-adrenoceptor is less accessible to exogenously administered agonists and antagonists.…”
Section: Discussionmentioning
confidence: 99%
“…Although noradrenaline (NA) is present in high concentrations in sympathetic nerve terminals, NA does not mediate all the postjunctional responses elicited by sympathetic nerve stimulation (Ambache & Zar, 1971;Burnstock, 1986). Studies on guinea-pig submucosal arterioles have shown that both the underlying changes in membrane potential (excitatory junction potentials, ej.ps) and vasoconstrictions following short trains of low or high frequency stimulation of the sympathetic nerves are unaffected by ax-adrenoceptor antagonists (Hirst & Neild, 1980;1981;Shen et al, 1990).…”
Section: Introductionmentioning
confidence: 99%